Tech-Enhanced Learning: Assessing the Impact of an Innovative Microlearning Module on Postgraduate Students’ Perceptions and Academic Progress - Naser, Khadijeh Mohammad (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The current study uses the lens of Robert Gagne’s nine events of instruction and the flipped classroom approach to construct a proposed educational module to teach the instructional technology course for preservice teachers at Al Ain University in UAE. The content was broken down into small parts and presented to students through videos and interactive learning exercises. A quasi-experiment was conducted to study the designed module’s effectiveness. The sample involved two groups of 50 female postgraduates from different fields of specialization. The experimental group students were taught through the implementation of the flipped microlearning module, while the control group was taught the same way, except that the educational content was conveyed without chunking. The researcher collected data by administering an achievement test and using the UTAUT questionnaire to determine student acceptance of the module. The result of the ANCOVA test revealed the existence of a substantial difference between the two groups, as f reached 4.427 in favor of the experimental group, with a significance level of 0.038. The questionnaire findings indicated high student acceptance of the module. The findings are of great importance for educational policy and curriculum designers and highlight the advantages of this module in enhancing student performance in different specialist fields.